Strategi Kepala Sekolah Dalam Meningkatkan Iklim Organisasi Yang Kondusif Di SMA Negeri Surulangun Kabupaten Musi Rawas Utara - Karmila, Surya; nur sasongko, rambat; somantri, Manap (Manajer Pendididikan, 2025)
The research objective is to see the principal's strategy in improving a conducive organizational climate in SMA Negeri Surulangun which includes three aspects, namely the relationship between the principal and the teacher, the relationship between teachers, the relationship between the principal and the committee. The research method used a qualitative approach. The results of the research by principals applying an open communication system, involving school members in making decisions, providing opportunities for self-development, supervising motivation, holding teacher self-development support facilities, aligning teacher ratings when making decisions, providing equal opportunities to take further education, activity activities community, raising social assistance funds, involving community leaders in activities and supervision of students outside of school